CHARACTERISTICS OF AMARANTH VARIETIES OF VNIISSOK BREEDING FOR RESISTANCE TO LOW TEMPERATURE AND FIELD MOISTURE DEFICIENCY AT CULTIVATION IN THE MOSCOW REGION AND THE REPUBLIC OF ECUADOR - M. S. Gins; V. K. Gins; K. H. Torres Mino (Овощи России, 2015)
Analysis of morphological and physiological characters of amaranth varieties of VNIISSOK and Ecuador breeding grown under optimal conditions, as well as at low temperature and precipitation deficit showed a reduction in height, number of leaves and inflorescence length to different extents. It points to the different resistance of varieties to the unfavorable environmental factors.